KEPUASAN MASYARAKAT TERHADAP PROGRAM TANGGUNG JAWAB SOSIAL PERUSAHAAN (TJSL) ECOBRICK PT PERTAMINA PATRA NIAGA INTEGRATED TERMINAL PANJANG - Ayu Nirmala Lutfie Syarief; Titon Srihardian; Samino; Bayu Aji Pamungkas; Rinda Aryani Putri (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2026)
ABSTRACT Siaga and Clean CSR is a program that focuses on disaster response and environmental cleanliness education activities, especially in waste management. The background to the formation of this innovation program is because the condition of waste management in the area around IT Panjang, namely North Panjang Subdistrict, is still facing various challenges, including delays in waste transportation. Piled and unmanaged waste is 32 tons in Panjang District. The development of the Siaga and Clean CSR Program in the Panjang Utara Subdistrict area aims to address the problem of environmental vulnerability due to the accumulation of waste that is not well managed through the development of a waste processing program. The Siaga and Clean CSR Program has been able to provide beneficial value to society. The impact and benefit values ​​are measured through a sustainability compass which consists of four (4) sustainability aspects including economic, social, nature and well-being. Economic aspects include income from maggot sales of Rp 2,000,000- Rp 4,800,000/month and income from ecobrick sales of Rp 500,000-Rp 3,000,000/month. Natural aspects include 63 kg/year reduction in plastic waste, 0.189 ton CO₂/year reduction in carbon emissions from processing plastic waste, 8,640 kg/year, reduction in organic waste used for maggot cultivation, 194.4 kg CH4/year, reduction in methane emissions in processing organic waste, 388.8 kWh/year, total savings in lighting energy for 3 lamps and the installation of 50 biopores. The social aspect includes the emergence of 1 (one) new group, namely the Ruggot (Maggot House) group. Siaga and Clean CSR Program has involved relevant stakeholders such as the Bandar Lampung City Environmental Service and the Bandar Lampung City BPBD in program development. Welfare aspects include, among others, waste management which has empowered local beneficiary groups, as many as 175 families have benefited from the existence of the Siaga and Clean CSR Program, as many as 10 women, including socio-economically vulnerable women one of whom is widows, poor people and the unemployed, have been educated about the use of inorganic and organic waste.